The Evidence-Based Leadership on Higher Education: A Theorical Review - Alamsyah, Virza Utama (International Journal of Social and Management Studies, 2021)
The world of education is facing serious challenges that will impact the future of students in devastating ways. This study was created to examine critical theories to test Educational Leadership in carrying out evidence-based leadership that rests on the potential of leaders to be able to do coaching and build a positive-associative culture by developing an attitude of sustainability innovation. Evidence-based educational leadership theory requires an immediate change in thinking that institutions education, which plays an important role in developing and safeguarding stakeholders, redefines the role of educational leadership as a social practice in a rapidly changing world.